Determination of shear strength values for granular backfill material used by the Wisconsin Department of Transportation - Edil, Tuncer; Bareither, Christopher A.; Benson, Craig H. (Wisconsin Highway Research Program, 2007)
This study will determine the correlation of various properties and conditions to the friction angle values. Investigation will also determine the variation in these values and recommend allowable design values for the various materials commonly used for backfill for walls and reinforced slopes.
151 p.
Keywords: Friction; Sandstones; Trench backfill; Earth walls; Shear strain; Engineering geology; Shear strength; Granular soils; Grain size (Geology)